Review of watermarking techniques for medical images - Ghazali, Naseem H. (Research India Publications, 2015)
Recent advancement of technologies has resulted in radical change of medical imaging facilities and medical information systems. These advances introduce new legal and ethical issues particularly during the storing and transmission of medical data and images over open networks. Recent works show the possibility of using digital watermarking to solve the security issues regarding the confidentiality, authenticity, and integrity of electronic medical records. Thus, this paper presents an updated review of the watermarking techniques for medical image applications. The concepts of digital watermarking as well as its variants are firstly introduced to give an in-depth understanding of this field. This is followed by a brief introduction to medical imaging and DICOM format. The review also discussed some of the existing techniques on medical image watermarking.